2016
DOI: 10.1016/j.nanoen.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer MoS 2 /GaAs heterostructure self-driven photodetector with extremely high detectivity

Abstract: Two dimensional material/semiconductor heterostructures offer alternative platforms for optoelectronic devices other than conventional Schottky and p-n junction devices. Herein, we use MoS 2 /GaAs heterojunction as a self-driven photodetector with wide response band width from ultraviolet to visible light, which exhibits high sensitivity to the incident light of 635 nm with responsivity as 446 mA/W and detectivity as 5.9×10 13 Jones (Jones = cm Hz 1/2 W -1 ), respectively. Employing interface design by inserti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(97 citation statements)
references
References 46 publications
1
96
0
Order By: Relevance
“…The 2D/3D p–n heterojunction is a relatively common structure, devised by depositing 2D nanosheet materials on a bulk substrate of Si or GaAs to construct a 2D–3D p–n heterojunction photodetector . Xu et al reported a 2D/3D MoS 2 /GaAs p–n heterojunction self‐powered photodetector that deposits MoS 2 nanosheets on bulk GaAs substrates ( Figure a). The MoS 2 /GaAs p–n heterojunction has a wide response bandwidth from ultraviolet to visible light and exhibits a self‐driven optical responsivity of 321 mA W −1 and a photoresponse time of 17 µs under 635 nm light irradiation.…”
Section: D Material‐based P–n Junction Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2D/3D p–n heterojunction is a relatively common structure, devised by depositing 2D nanosheet materials on a bulk substrate of Si or GaAs to construct a 2D–3D p–n heterojunction photodetector . Xu et al reported a 2D/3D MoS 2 /GaAs p–n heterojunction self‐powered photodetector that deposits MoS 2 nanosheets on bulk GaAs substrates ( Figure a). The MoS 2 /GaAs p–n heterojunction has a wide response bandwidth from ultraviolet to visible light and exhibits a self‐driven optical responsivity of 321 mA W −1 and a photoresponse time of 17 µs under 635 nm light irradiation.…”
Section: D Material‐based P–n Junction Photodetectorsmentioning
confidence: 99%
“…a) Schematic structure of the MoS 2 /GaAs photodetector. Reproduced with permission . Copyright 2016, Elsevier.…”
Section: D Material‐based P–n Junction Photodetectorsmentioning
confidence: 99%
“…Among all semiconducting NWs, III–V semiconductor NWs are promising candidates for photodetectors because of their high absorption coefficient and wide tunable bandgaps . Photodetectors based on III–V semiconductor NWs have been fabricated in different configurations such as core–shell nanostructures, alloys, and heterostructures . Among all III–V NWs, gallium arsenide (GaAs) NWs have gained immense attention for detection application over recent years because of their high light‐to‐electricity conversion efficiency, moderate direct bandgap (1.42 eV), and high compatibility with Si technology, which in turn make them suitable for various outstanding optoelectronic applications like solar cells, photodetectors, p‐n diodes, and field effect transistors …”
Section: Comparison Of Responsivity Optical Gain and Detectivity Ofmentioning
confidence: 99%
“…[64] (f) Current density-voltage curves of MoS2/GaAs heterojunction under dark and illumination. [64] Fig . 5a shows the device geometry fabricated by Wang et al [61] The MoS2 film was deposited on the p-Si substrate with a predefined SiO2 window by magnetron sputtering.…”
Section: Heterojunctions Based On Tmdcs Conventional Bulk Semiconducmentioning
confidence: 99%